Cambios cíclicos de los niveles de 17-b estradiol y de progesterona circulantes en sangre periférica del venado (odocoileus virginianus gymnotis) determinados por radioinmunoensayo (1988)
Gonadal steroids were determined by Radioinmuneassay in two females white-tailed deer, Odocoileus virginianus gymnotis. The ovarian cycles were between 21 and 31 days (average 24 ± 3.46 days) with luteal and follicular phases from 11.33 :!: 5.55 and 12.6 ± 2.8 days, respectively.